The impact of COVID‐19 pandemic‐related stress experienced by Australian nurses. (11th October 2021) - Aggar, Christina; Samios, Christina; Penman, Olivia; Whiteing, Nicola; Massey, Deb; Rafferty, Rae; Bowen, Karen; Stephens, Alexandre
Abstract: Globally, the impact of COVID‐19 on healthcare workers' mental health has been a major focus of recent research. However, Australian research involving nurses, particularly across the acute care sector, is limited. This cross‐sectional research aimed to explore the impact of pandemic‐related stress on psychological adjustment outcomes and potential protective factors for nurses ( n = 767) working in the Australian acute care sector during the COVID‐19 pandemic. Nurses completed an online questionnaire with psychometrically validated measures of pandemic‐related stress, psychological adjustment outcomes (depression, anxiety, and subjective well‐being), and protective factors (posttraumatic growth and self‐compassion). Descriptive analyses revealed that pandemic‐related stress was reported by 17.7% of the participants. Psychological adjustment outcome scores above normal for depression (27.5%) and anxiety (22.0%) were found, and 36.4% of the participants reported poor subjective well‐being. Regression analyses suggest that pandemic‐related stress predicted greater depression ( B = 0.32, SE = 0.02, 95% confidence interval [0.28, 0.35]) and anxiety ( B = 0.26, SE = 0.01, 95% confidence interval [0.24, 0.29]) and less subjective well‐being ( B = −0.14, SE = 0.01, 95% confidence interval [−0.16, −0.12]). Self‐compassion weakened the relationship between pandemic‐related stress and greater depression, however, exacerbated the relationship between pandemic‐related stress and less subjective well‐being. Posttraumatic growth reduced the negative relationship between pandemic‐related stress and psychological adjustment outcomes. These findings will inform strategies to facilitate psychological resources that support nurses' psychological adjustment, enabling better pandemic preparedness at both an individual and organizational level.